PENGARUH HAMBATAN NONTARIF DI PASAR UNI EROPA TERHADAP EKSPOR KOMODITAS CPO INDONESIA - Gumelar, Satria Arif; Affandi, Muhammad Irfan; Situmorang, Suriaty (Lampung University, 2020)
This research aims to analyzewhich tariff and non-tariff barriersare implemented by European Union (EU) on Indonesian Crude Palm Oil (CPO), whether the non-tariff barrier named ?Report on Palm Oil and Deforestation of Rainforest? which has been ratified by the European Commission (EC) have a significant effects on Indonesian CPO export, and bargaining positionof Indonesian CPO in vegetable oils market. This research used secondary data obtained from BPS, Indonesian National Export Development Agency, Central Bank of Indonesia, Eurostat, WTO, FAO, and supported by interviews with Indonesian Ministry of Trade and Indonesian Palm Oil Association (IPOA). The results showed that the EU imposed tariff barriers that varied between 3.8 - 15%. However, tariff barriers were not appliedfor CPO with HS code 1511101000. The EU has implemented non-tariff barriers on Indonesian CPO since 1905 with various kinds of issues such as health, social and environment. The non-tariff barrier which was ratified in April 2017 by the EC does not significantly affect Indonesian CPO export, but it causes reduction on palm oil prices in Indonesia. Bargaining position of Indonesian CPO in the CPO trade to EU was still powerful compared with othervegetable oils such as Rapeseed Oil (RSO), Sunflower Oil (SFO), and Soybean Oil (SBO).Keywords:CPO, european union, non-tariff barriers.